2008
DOI: 10.1128/cvi.00056-08
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Testing of Large Pools of Mycobacterium tuberculosis RD1 Peptides and Identification of Major Antigens and Immunodominant Peptides Recognized by Human Th1 Cells

Abstract: Tuberculosis (TB) is among the most important diseases of worldwide distribution with respect to both morbidity and mortality. Annually, TB afflicts about 9 million people with 2 million deaths (18). The rapid spread of TB in developing countries of Africa and Asia is accelerated by the human immunodeficiency virus epidemic and the spread of multi-and extra-drug-resistant TB (46). To protect against TB, vaccination with Mycobacterium bovis BCG has been used for more than 70 years, but its efficacy varies treme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 46 publications
6
67
1
Order By: Relevance
“…Several reports have suggested that IFN-␥ and IL-17 production by CD4 ϩ T cells is targeted in vaccine-induced immunity to M. tuberculosis infection in mouse models (34,35). The immunogenic IFN-␥-generating T-cell epitopes in PE/PPE family proteins are potential TB vaccines (30) and diagnostic biomarkers (36). In this study, two predominant epitope sites were demonstrated by strong IFN-␥-inducing T cells at amino acids 85 to 102 and 217 to 234.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that IFN-␥ and IL-17 production by CD4 ϩ T cells is targeted in vaccine-induced immunity to M. tuberculosis infection in mouse models (34,35). The immunogenic IFN-␥-generating T-cell epitopes in PE/PPE family proteins are potential TB vaccines (30) and diagnostic biomarkers (36). In this study, two predominant epitope sites were demonstrated by strong IFN-␥-inducing T cells at amino acids 85 to 102 and 217 to 234.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that RD1 was the most important region encoding proteins with Th1-cell reactivity , 2010Mustafa & Al-Attiyah, 2009;Mustafa et al, 2011). The analysis of individual peptide pools of RD1 ORFs identified three major (Rv3873, Rv3874 and Rv3875) and three moderate (Rv3871, Rv3872 and Rv3876) antigens stimulatory for Th1 cells in antigeninduced proliferation and IFN-γassays Mustafa 2005b;Mustafa et al, 2008). However, Rv3873 and Rv3876 proteins were equally good stimulators of Th1 cells from TB patients and healthy donors, whereas Rv3872, Rv3874, Rv3875 proteins were better stimulators in TB patients and Rv3871 protein in healthy donors .…”
Section: Identification Of M Tuberculosis-specific Genomic Regions Amentioning
confidence: 99%
“…Interestingly, previous studies using pools of synthetic peptides have shown that all of these proteins (Rv3874, Rv3875 and Rv3619c) are major T cell antigens in humans, and the linear T cell epitopes were scattered throughout the sequence of these proteins Mustafa et al 2000Mustafa et al , 2008. A further analysis of the sequence of these proteins for B cell and T cell epitope prediction using appropriate prediction servers further suggested that B-cell and T-cell epitopes were scattered throughout the sequence of each protein (Hanif et al, 2010a;Mustafa et al, 2008;Mustafa and Shaban, 2006). Thus, both prediction and experimental results confirm the strong immunogenicity of Rv3874, Rv3875 and Rv3619c proteins for inducing antigen-specific immunological reactivity.…”
Section: Molecular Cloning Expression Purification and Immunologicamentioning
confidence: 99%
“…Furthermore, testing with peripheral blood mononculaer cells for cellular reactivity in T cell assays identified three proteins of RD1, i.e. PPE68, ESAT6 and CFP10, and two proteins each of RD7 (Rv2346c and Rv2947c) and RD9 (Rv3619 and Rv3620) as the best stimulators of T helper 1 (Th1) cells in antigen-induced proliferation and/or IFN-γ secretion assays [18][19][20][21][22][23].The diagnostic potential of four antigens encoded by M. tuberculosis-specific RD1 region genes (PE35, PPE68, CFP10, ESAT-6) and RD9 region gene Rv3619c was further investigated in cellular assays using DTH responses in guinea pigs [24]. The results showed that mycobacterial sonicates containing species-specific and crossreactive antigens, induced positive DTH responses in M. tuberculosis, M. bovis BCG, M. avium and M. vaccae injected guinea pigs.…”
mentioning
confidence: 99%
“…Furthermore, testing with peripheral blood mononculaer cells for cellular reactivity in T cell assays identified three proteins of RD1, i.e. PPE68, ESAT6 and CFP10, and two proteins each of RD7 (Rv2346c and Rv2947c) and RD9 (Rv3619 and Rv3620) as the best stimulators of T helper 1 (Th1) cells in antigen-induced proliferation and/or IFN-γ secretion assays [18][19][20][21][22][23].…”
mentioning
confidence: 99%